College algebra - Reyes, Fe N.; Marasigan, Jose A. (Quezon City, Philippines : JMC Press Inc., 1982)
A first course in "College Algebra" is normally taken by the entering college freshman who is enrolled in one of the many curricula leading to an arts or sciences degree or to a professional degree.
The Real Numbers -- The Algebra of Polynomials -- Functions and their Graphs -- Linear Functions, Equations and Inequalities -- Systems of Linear Equations and Inequalities -- Quadratic Functions and Quadratic Equations -- Polynomial Functions and Theory of Polynomial Equations -- Exponential and Logarithmic Functions -- Elementary Combinatorics.
Includes Index.
Keywords: ALGEBRA